2006
DOI: 10.1186/1471-230x-6-32
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured appendiceal cystadenoma presenting as right inguinal hernia in a patient with left colon cancer: A case report and review of literature

Abstract: Background: Mucoceles resulting from cystadenomas of the appendix are uncommon. Although rare, rupture of the mucoceles can occur with or without causing any abdominal complaint. There are several reports associating colonic malignancy with cystadenomas of the appendix. Herein, we report an unusual and interesting case of right inguinal hernia associated with left colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
12
0
3
Order By: Relevance
“…16 Lee et al first described their abnormal colonoscopy findings in a patient with pseudomyxoma peritonei. 22 We are unaware of a large series that adequately describes the preoperative colonoscopic findings in patients presenting with appendiceal adenocarcinoma with pseudomyxoma peritonei. Thus, the aim of this study was to determine the diagnostic yield of colonoscopy in detecting previously diagnosed appendiceal adenocarcinoma with pseudomyxoma peritonei and to characterize the mucosal abnormalities associated with appendiceal adenocarcinoma with pseudomyxoma peritonei.…”
Section: Introductionmentioning
confidence: 98%
“…16 Lee et al first described their abnormal colonoscopy findings in a patient with pseudomyxoma peritonei. 22 We are unaware of a large series that adequately describes the preoperative colonoscopic findings in patients presenting with appendiceal adenocarcinoma with pseudomyxoma peritonei. Thus, the aim of this study was to determine the diagnostic yield of colonoscopy in detecting previously diagnosed appendiceal adenocarcinoma with pseudomyxoma peritonei and to characterize the mucosal abnormalities associated with appendiceal adenocarcinoma with pseudomyxoma peritonei.…”
Section: Introductionmentioning
confidence: 98%
“…In 16 of the patients, a laparotomy was performed following the identification of mucin with a variety of additional procedures. A detailed review of the literature identified only two cases, such as ours, in which atypical features of the hernia together with vague gastrointestinal symptoms lead to preoperative evaluation and diagnosis of pseudomyxoma peritonei 7 8…”
Section: Discussionmentioning
confidence: 94%
“…Salemis et al [14] reported an appendiceal villous adenoma, while there are also only a few cases of cystadenomas of the appendix [15, 16]. Moreover, appendiceal adenocarcinomas within an Amyand's hernia are rarely observed [4, 5].…”
Section: Discussionmentioning
confidence: 99%